(untitled) (Jurnal Geomine, 2022)
Sumatra has long been recognized as the interacting region between Indo-Asutralian plate and Eurasian plate, hence the tectonic deformation occurring in the island may have affected by the converging movement of these plates. This study focuses on evaluation of the tectonic structures developed in the Muaro region by integrating the field data and the lineament pattern interpreted from Digital Elevation Model (DEM). Study area is situated within the Ombilin basin, known as the intramontane basin that formed due to transtensional movement of the Sumatran fault system. The DEM image used to identify structure is that of DEMNas, which has been extracted on ArcGIS 10.3 and PCI-Geomatica. The results of interpretation reveal that the alignment shows a general orientation northwest-southeast, which is parallel to a structural pattern of the Kabun anticline, the Silokek syncline, and the Kabun fault. The consistency in orientation between the lineament pattern and the structural trend indicates that the direction of tectonic forces responsible for the deformation of rock sequence was likely northwest-southeast.